Rhynchosia ngwenyii (Phaseoleae, Fabaceae), a new species of Rhynchosia from South Africa - Ajao, Abdulwakeel Ayokun-Nun; Jaca, Thulisile Precious; Moteetee, Annah Ntsamaeeng (Phytotaxa, 2020)
During the examination of the rich collections of the genus, Rhynchosia housed in some South African herbaria (BNRH, NH, PRE), a new and yet to be described species was discovered. The species is similar to R. pauciflora in its erect habit, linear or oblong leaflets, and solitary flowers. The study is based on the examination of herbarium specimens. Measurements were taken from vegetative and reproductive parts. We describe here R. ngwenyii. The new species differs from R. pauciflora by its broader (24–38 mm), linear-lanceolate to oblong-lanceolate terminal leaflets that are without conspicuous revolute margins, wing petals that lack sculpturing and shorter peduncles, (25)30–42 mm. It is distributed in KwaZulu-Natal and Mpumalanga Provinces in South Africa. The preliminary conservation status is evaluated as Endangered. A detailed description, illustration, distribution map, and the information on ecology, as well as phenology are also presented.